BATAS USIA NAFKAH ANAK BERDASARKAN MAQĀSID AL-SYARI‘AH - Marwan Marwan (Islam Futura, 2014)
The stipulation of the age limit of child’s livelihood based on to the number of year is important to do, because standard of age maturity (not child authonomy) that has been used can lead to the harm to the child who has been in age maturity but she or he is not authonomous yet. On the other hand, the lack of independent age limit can be burden to the parents, because granting a living become limitless. The age limit is not available through the texts of the Shari‘a, therefore, it should be studied by using uṣūl al-fiqh approach (maqāṣid al-syarī‘ah). This study use mixed method; deductive and inductive. The findings were analyzed by using istiṣlāḥiyyah reasoning patterns. Based on this study, it was concluded that the limit of liability of parents for their children is until the child reaches the age of 23 years, because at the age of 22 years, children in Indonesia generally have completed undergraduate. So at least it takes a year to prepare for finding a job to pay for his life before actually independent living. In addition, there are companies in Indonesia generally limits the prospective new employee at the age of 25 years.